Production and characterisation of pyrolysis oil from discarded medical plastic (syringe) waste with common rail direct injection engine assessment - Thamizhvel, Rajkumar; Vaithianathan, Natarajan; Sethuraman, Narayanan; Vinodraj, Subramanian; Ambetharasu, Lenin; Ambetharasu, Lenin; Surendar, Palani (Archives of Thermodynamics, 2026)
This study explores the potential of converting syringe plastic waste into an alternative fuel through pyrolysis. Since sy-ringes are primarily made of polypropylene, they were thermally decomposed in a batch reactor, producing a maximum pyrolysis oil yield of 76% at 400–500°C. The produced syringe plastic oil (SPO) was characterised for key fuel properties and blended with diesel at 20%, 30%, and 40% proportions. The performance of the engine and the emission characteristics of these blends were tested experimentally on a common rail direct injection diesel engine. Of the fuels tested, the D80SPO20 mixture proved to be as efficient as diesel with the brake thermal efficiency of 26.9% and brake specific fuel consumption of 0.27 kg/kWh at full load. This mixture was also found to result in a significant reduction in carbon mon-oxide, hydrocarbons and smoke emission with a slight increment in NOx relative to diesel. On the whole, the findings show that low-percentage SPO30, especially D80SPO20, provide a favourable combination between engine efficiency and emis-sion reduction, proving the potential of the syringe plastic pyrolysis oil as a sustainable alternative of diesel fuel in part.